1998
DOI: 10.1046/j.1469-0705.1998.12010033.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular filling in normally grown fetuses, growth‐restricted fetuses and fetuses of diabetic mothers

Abstract: There is a delay in left ventricular filling which may reflect changes in myocardial relaxation and possible reduction in passive ventricular filling as a result of chronic hypoxemia in the SGA fetus and altered in utero metabolic environment in the IDDM fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 17 publications
0
43
0
3
Order By: Relevance
“…The normal E/A ratio during pregnancy is below 1, which means that the fetal myocardium is relatively "stiff" compared to that of newborns and older children (16)(17)(18)(19)(20)(21)(22). An increase or inversion of the E/A ratio is related to ventricular diastolic dysfunction (23)(24)(25)(26)(27). There are few reports of other parameters used to evaluate ventricular diastolic function in the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The normal E/A ratio during pregnancy is below 1, which means that the fetal myocardium is relatively "stiff" compared to that of newborns and older children (16)(17)(18)(19)(20)(21)(22). An increase or inversion of the E/A ratio is related to ventricular diastolic dysfunction (23)(24)(25)(26)(27). There are few reports of other parameters used to evaluate ventricular diastolic function in the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tsyvian et al 12 , in addition to myocardial hypertrophy in fetuses of diabetic mothers, an alteration in left ventricular filling occurs between the 20th and 36th gestational weeks. Left ventricular filling depends on myocardial diastole and is modified by several factors.…”
Section: Discussionmentioning
confidence: 99%
“…Rizzo et al 13 reported a reduction in diastolic function in fetuses of diabetic mothers expressed by this ratio. A reduced ventricular compliance in fetuses of diabetic mothers could be secondary to wall thickening or to other factors, such as metabolic alterations in the uterine environment associated with qualitative changes in collagen (an increase in the fluorescent collagen in the myocardium) 12 . The higher E wave velocity in mitral and tricuspid valves in the group of fetuses of diabetic mothers with myocardial hypertrophy found in this study could reflect an altered pattern of relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations